The Effect of Work Communication And Work Discipline on Employee Performance at PT Si Cepat Ekspres Indonesia - Whina Ratnawati (Journal of Research in Business, Economics, and Education, 2021)
The purpose of this study was to determine work communication and work discipline on employee performance at PT Sicepat Ekspres Indonesia. The method used is quantitative. The sampling technique used is a sample of 69 respondents. Data analysis using validity test, reliability test, correlation coefficient, analysis of the coefficient of determination or determinant coefficient, simple linear regression test, multiple linear regression analysis, hypothesis testing / correlation coefficient significance test (t test). The results of the research results starting from theoretical exposure to data collection and data presentation as well as analysis and discussion, it can be concluded , , H0 is rejected and Ha is accepted, this shows that there is a significant influence between work communication on the performance of employees of PT. Sicepat Express Indonesia Central Jakarta. And H0 is rejected and Ha is accepted, this shows that there is a significant influence between work discipline on the performance of PT. Sicepat Express Indonesia Central Jakarta.